Evolution of neurologic symptoms in non‐hospitalized COVID‐19 "long haulers". Issue 7 (24th May 2022) - Ali, Sareen T.; Kang, Anthony K.; Patel, Tulsi R.; Clark, Jeffrey R.; Perez‐Giraldo, Gina S.; Orban, Zachary S.; Lim, Patrick H.; Jimenez, Millenia; Graham, Edith L.; Batra, Ayush; Liotta, Eric M.; Koralnik, Igor J.
Abstract: Objective: We characterized the evolution of neurologic symptoms and self‐perceived recovery of non‐hospitalized COVID‐19 "long haulers" 6–9 months after their initial Neuro‐COVID‐19 clinic evaluation. Methods: In this follow‐up study on the first 100 patients, 50 SARS‐CoV‐2 laboratory‐positive (SARS‐CoV‐2 + ), and 50 laboratory‐negative (SARS‐CoV‐2 − ), evaluated at our Neuro‐COVID‐19 clinic between May and November 2020, patients completed phone questionnaires on their neurologic symptoms, subjective impression of recovery and quality of life. Results: Of 52 patients who completed the study (27 SARS‐CoV‐2 +, 25 SARS‐CoV‐2 − ) a median 14.8 (range 11–18) months after symptom onset, mean age was 42.8 years, 73% were female, and 77% were vaccinated for SARS‐CoV‐2. Overall, there was no significant change in the frequency of most neurologic symptoms between first and follow‐up evaluations, including "brain fog" (81 vs. 71%), numbness/tingling (69 vs. 65%), headache (67 vs. 54%), dizziness (50 vs. 54%), blurred vision (34 vs. 44%), tinnitus (33 vs. 42%), and fatigue (87 vs. 81%). However, dysgeusia and anosmia decreased overall (63 vs. 27%, 58 vs. 21%, both p  < 0.001). Conversely, heart rate and blood pressure variation (35 vs. 56%, p  = 0.01) and gastrointestinal symptoms (27 vs. 48%, p  = 0.04) increased at follow‐up. Patients reported improvements in their recovery, cognitive function, and fatigue, but quality of life measures remained lower than the US normative population ( p  < 0.001). SARS‐CoV‐2 vaccination did not have a positive or detrimental impact on cognitive function or fatigue. Interpretation: Non‐hospitalized COVID‐19 "long haulers" continue to experience neurologic symptoms, fatigue, and compromised quality of life 14.8 months after initial infection.